The influence of Total Quality Management on firms' intellectual capital - Emilio Ruiz; Jesus D. Sanchez De Pablo; Rosa M. Mu\~noz; Isidro Pe\~na (South African Journal of Business Management, 2018)
Background: After carrying out an extensive literature review, it is clear that Total Quality Management (TQM) has a significant influence on many areas of companies. The development of quality management practices can lead to the generation of intellectual capital and thus become a key competitive factor.Objectives: The purpose of this research was to explore whether TQM practices have a positive influence on a company's intellectual capital.Method: We formulate three hypotheses considering the components of intellectual capital: human capital, social capital and organisational capital. This article develops an empirical analysis through the use of structural equation modelling using the partial least squares technique.Results: The results show that TQM has a strong positive causal effect on intellectual capital.Conclusion: This research, therefore, identifies a key determinant of one of the most important strategic variables for companies at present: intellectual capital.
Keywords: 650